Clinical and biochemical studies on zinc deficiency (hypozincemia) of goat and sheep - Khaleel Zainel Khaleel (Kufa Journal for Veterinary Medical Sciences, 2013)
Clinical, and some biochemical parameters have been studied in local sheep and goat affected naturally with hypozincemia in Al-Najaf province, Iraq. The study was conducted on 25 local Iraqi sheep and 15 goat, the age of these animals were between 1-2 year old. Twenty  clinical healthy sheep of the same ages were used as control. Affected sheep and goat showed signs of alopecia (36.36% , 27.27% )  abnormal skin (rough, thickened, wrinkled, cracked and dandruff ) (45.45% , 27.27% ), paleness of mucous membranes (63.63% , 36.36% ),  loss of appetite (63.63% , 36.36% ), decreased growth rate (36.36% , 18.18% ), swelling of joints (18.18% , 9.09%) and pica (9.09% , 9.09% ) respectively. No significant difference has been detected in body temperature, whereas respiratory and heart rates were significantly increased in affected animals in comparison with control. The biochemical results revealed significant decrease in serum zinc and alkaline phosphatase  level in diseased animals than in control one.